Penyuluhan dan Internalisasi Faham Ahlussunnah Wal Jama’ah Untuk Meningkatkan Pemahaman Aqidah Peserta Didik di SDN Besowo 5 Kediri - Achmad Mujahidin; Ahmad Ainun Naim (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2023)
Nowadays, having tolerant and flexible traits in socio-cultural and religious in a compound environment is very important for students to have. Because in forming a good and obedient Muslim person, students should follow the example of what was done by the Prophet SAW and the Companions of the Prophet SAW. in spreading the spirit of Islam lil 'alamiin (mercy for the entire universe) to all corners of the world in order to embrace and spread Islam in a friendly and full of rahmah (affection), not with threats and anger. Therefore, the understanding of Ahlussunnah wal Jamaah for students who are muslim in particular, is very important to understand and learn. In the study itself, the author chose to use the PAR (Participatory Action Research) method. The first step taken by the researcher is to prepare the material to be delivered. The second step is to carry out the process of counseling and internalization. And the last step is to evaluate the counseling and internalization that has been carried out from beginning to end to students. The results showed that, the process of counseling and internalizing Aswaja understanding to students, can have a significant impact on them, as well as the social environment around them.